2016
DOI: 10.1097/gox.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Morbidities of Bone Graft Harvesting from the Olecranon Process and the Distal Radius

Abstract: Background:The aim of this study is to compare donor-site morbidities between patients who underwent bone graft harvesting from either the olecranon process (OP) or the distal radius (DR).Methods:We evaluated 44 patients who underwent bone graft harvesting from the OP (25 cases) or the DR (19 cases) for various procedures in the ipsilateral upper extremity. Follow-up averaged 14 (OP group) and 19 months (DR group). Outcome measures included visual analog scales (VAS) for graft harvest-site pain and scar appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…30 One study reported no significant differences in VAS scores for pain, scar appearance, and function between olecranon bone grafting and distal radius bone grafting. 50 Scaphoid nonunion requires rigid fixation to facilitate primary bone healing. A meta-analysis of fixation for scaphoid nonunion showed that nonvascularized bone grafting with screw versus K-wire fixation provides comparable union rates of 90% versus 88%.…”
Section: Discussionmentioning
confidence: 99%
“…30 One study reported no significant differences in VAS scores for pain, scar appearance, and function between olecranon bone grafting and distal radius bone grafting. 50 Scaphoid nonunion requires rigid fixation to facilitate primary bone healing. A meta-analysis of fixation for scaphoid nonunion showed that nonvascularized bone grafting with screw versus K-wire fixation provides comparable union rates of 90% versus 88%.…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient (1.8%) had residual donor site pain at 6 months. 9 Donor site pain is one of the most frequent complications associated with iliac crest bone grafting (ICBG) and almost 100% subjects experienced some kind of pain at various follow-ups. Donor site pain was evaluated using VAS, a common measure to assess the pain.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Micev et al observed no statistical differences on comparing the use of graft harvested from the olecranon and distal radius regarding pain, consolidation, and complications of both techniques. 17 Recently, Yang et al conducted an anatomical study of the removal of a vascularized graft from the olecranon based on the recurrent posterior ulnar artery for complex defects requiring a structured and vascularized bone supply. 27 …”
Section: Discussionmentioning
confidence: 99%